2017
DOI: 10.1097/iio.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Tear Volume-based Diagnostic Classification for Tear Dysfunction

Abstract: Dysfunction of one or more components of the lacrimal functional unit results in an unstable tear film that can trigger eye irritation or cause ocular surface disease. There are distinct differences in the pattern of cornea and conjunctival disease and inflammation between aqueous deficient and aqueous sufficient tear dysfunction. There are accurate commercially available methods to measure tear volume. Diagnostic classification based on tear volume can guide therapy and identify patients with higher risk of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We also found that the number of goblet cells was reduced in the conjunctival epithelium from 15-month-old M3R −/− mice. Previous studies in humans reported that aqueous deficiency causes dysfunction and loss of conjunctival goblet cells, while goblet cell number has been reported to remain within the normal range in Meibomian gland disease [ 3 ]. Likewise, desiccating stress was shown to induce conjunctival goblet cell loss in animal models [ 27 , 28 ], which is in part mediated by IFN-γ and CD4+ T cells [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the number of goblet cells was reduced in the conjunctival epithelium from 15-month-old M3R −/− mice. Previous studies in humans reported that aqueous deficiency causes dysfunction and loss of conjunctival goblet cells, while goblet cell number has been reported to remain within the normal range in Meibomian gland disease [ 3 ]. Likewise, desiccating stress was shown to induce conjunctival goblet cell loss in animal models [ 27 , 28 ], which is in part mediated by IFN-γ and CD4+ T cells [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…DED can be classified into aqueous deficient disease due to lacrimal hyposecretion, and into aqueous sufficient disease due to Meibomian gland disease or altered tear spread [ 1 ]. Previous studies have shown that aqueous deficiency causes dysfunction and loss of conjunctival goblet cells, while goblet cell number has been reported to remain in the normal range in Meibomian gland disease [ 3 ]. There are numerous causes for aqueous deficiency, such as aging, injury, anticholinergic medication, systemic inflammatory/immune diseases, e.g., Sjögren’s syndrome, as well as diseases that affect neural innervation or signaling [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding alterations of the location of Marx’s line, Pflugfelder et al . proposed that an anterior tear meniscus with concentrated osmolarity and inflammatory cytokines could affect differentiation of the MG orifices, causing squamous metaplasia of the lid margin 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Di Pascuale et al reported that spatial correlation of CCh with anterior migration of the mucocutaneous junction was a feature of MGD 34 . Regarding alterations of the location of Marx's line, Pflugfelder et al proposed that an anterior tear meniscus with concentrated osmolarity and inflammatory cytokines could affect differentiation of the MG orifices, causing squamous metaplasia of the lid margin 39 .…”
Section: Discussionmentioning
confidence: 99%